The Position of Customary (Adat) Lands in the Basic of Agrarian Law - Sembiring, Shindy Suka Desy Putri; Mahfud, Muh. Afif (Law Development Journal, 2023)
Fundamentally, the society in Indonesia is tied to customary lands issues. That thought is as the unity of the evidence on comprehending the customary lands confession. It is believed by the indigenous people as the sources of their life support or as the marking of their identities. Thus, nowadays the status of customary lands becomes the needs of solving the customary lands issues which is supposed to concern and do the integrated approach based on policy sourcing from a clear and fair rules of law both on UUPA or other regulations. This research is aimed to first, acknowledge the right of customary lands in Indonesia, the second is to acknowledge the status of customary lands on the rules of law which is on basic agrarian principles. The method used in this research is normative approach that is a descriptive. The sources of the data are from primary and secondary law material. The data gathering technique is by using literature study and qualitative data analysis. The result of this research shows that the right of customary lands for Indonesian society is really admitted by the rules which are not written or based on the customary confession as well with the alive traditional right which the existence is admitted. The right of customary lands status on UUPA has been approved, but that approval is still followed by certain term and conditions.